Review of Non-Discrimination Law in Education in Indonesia: Analysis Based on the Convention on the Rights of the Child - Khofi, Mohammad Bilutfikal (Rechtsvinding, 2024)
Education is a fundamental human right recognized in various national and international legal instruments. In Indonesia, the right to education is guaranteed by the 1945 Constitution and several other laws. However, discrimination in the education system remains a significant problem that hinders access and quality of education for all children. This research aims to explore non-discriminatory laws to protect education in Indonesia by referring to the standards set by the Convention on the Rights of the Child. The research method used is a literature review, which involves systematic observation of relevant research on discrimination in education in Indonesia. The research results show that Indonesia has established a legal framework for non-discriminatory education, including the 1945 Constitution, the National Education System Law, the Human Rights Law, and various other regulations, which explicitly prohibit all forms of discrimination in education. However, discrimination in education, whether based on SARA, gender, economic conditions, disability, or social status, is still a serious problem that hinders equal access and quality of education for all children in Indonesia.